2019
DOI: 10.1093/mnras/stz2428
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of lithium in the Milky Way halo, discs, and bulge

Abstract: In this work, we study the Galactic evolution of lithium by means of chemical evolution models in the light of the most recent spectroscopic data from Galactic stellar surveys. We consider detailed chemical evolution models for the Milky Way halo, discs and bulge, and we compare our model predictions with the most recent spectroscopic data for these different Galactic components. In particular, we focus on the decrease of lithium at high metallicity observed by the AMBRE Project, the Gaia-ESO Survey, and other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 74 publications
10
80
1
Order By: Relevance
“…The two bulge stars with the highest Li abundances at [Fe/H] ≈ +0.4 have A(Li) ≈ 2.8, and seem to continue on the declining A(Li) trend with [Fe/H] as outlined by the disk stars. Grisoni et al (2019) modelled the evolution of Li in the Milky Way and concluded that the main producer of Galactic Li is novae. By assuming that the fraction of binaries, which are supposed to be the novae progenitors, decrease with increasing metallicity, they also could provide an explanation for the decrease in A(Li) seen at the very highest metallicities.…”
Section: LI Metallicity and Agementioning
confidence: 99%
See 4 more Smart Citations
“…The two bulge stars with the highest Li abundances at [Fe/H] ≈ +0.4 have A(Li) ≈ 2.8, and seem to continue on the declining A(Li) trend with [Fe/H] as outlined by the disk stars. Grisoni et al (2019) modelled the evolution of Li in the Milky Way and concluded that the main producer of Galactic Li is novae. By assuming that the fraction of binaries, which are supposed to be the novae progenitors, decrease with increasing metallicity, they also could provide an explanation for the decrease in A(Li) seen at the very highest metallicities.…”
Section: LI Metallicity and Agementioning
confidence: 99%
“…The thin dash-dotted lines in Fig. 6 shows the models from Grisoni et al (2019) in which Li is produced by novae. There are several novae models shown, representing different laws for the fraction of binary systems that give rise to novae (see Grisoni et al 2019 for more details).…”
Section: LI Metallicity and Agementioning
confidence: 99%
See 3 more Smart Citations